SPE Reservoir Simulation Symposium 2013
DOI: 10.2118/163594-ms
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Wellbore Simulation of Flow Control Devices With Feedback Control for Thermal Operations

Abstract: Events such as hydraulic gradients in the horizontal completion, geologic and fluid variations in the reservoir and well placement issues can produce very poor steam conformance in the Steam Assisted Gravity Drainage (SAGD) process. Operators have implemented many strategies in an effort to address the issue. Simultaneous injection in inner tubing and annulus space or dual-tubing completions are commonly used in SAGD wells to provide controllable injection and production from the heel and toe regions of the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…., N) is the valve opening at the nth completed segment of the injection well, and e n (k) ϭ ⌬T n (k) Ϫ is the innovation (estimation) error. Given the input vector (13) to the neural network, the response of the jth hidden unit is calculated as (14) where (15) and j ϭ [ j0 , j1 , . .…”
Section: Identification and Continuous Update Of N Neural Network-basmentioning
confidence: 99%
“…., N) is the valve opening at the nth completed segment of the injection well, and e n (k) ϭ ⌬T n (k) Ϫ is the innovation (estimation) error. Given the input vector (13) to the neural network, the response of the jth hidden unit is calculated as (14) where (15) and j ϭ [ j0 , j1 , . .…”
Section: Identification and Continuous Update Of N Neural Network-basmentioning
confidence: 99%
“…Several numerical simulation studies have investigated the optimum design and location of the ICD implementation. Kyanpour and Chen have implemented reservoir simulation and wellbore modeling to determine the size and position of FCDs, considering reservoir heterogeneity. , Stone et al employed SAGD reservoir simulations to demonstrate the effectiveness of FCDs in improving steam distribution and boosting oil production when utilized in both injector and producer wells . Ghesmat and Zhao have presented general well-completion strategies using scab liners and FCDs for reservoirs with different structures .…”
Section: Introductionmentioning
confidence: 99%
“…32, 33 Stone et al employed SAGD reservoir simulations to demonstrate the effectiveness of FCDs in improving steam distribution and boosting oil production when utilized in both injector and producer wells. 34 Ghesmat and Zhao have presented general well-completion strategies using scab liners and FCDs for reservoirs with different structures. 35 Su and Gates used a numerical simulation and showed that ICDs provide a great uplift in homogeneous SAGD reservoirs.…”
Section: Introductionmentioning
confidence: 99%